Characterization of PECVD a-C:H:Si:O:Cl films - Rossi, Diego [UNESP]; Landers, Richard; Bortoleto, José R. R. [UNESP]; Durrant, Steven F. [UNESP] (American Vacuum Society, 2017)
Thin films were produced by plasma enhanced chemical vapor deposition of tetramethylsilane, chloroform, and argon mixtures. The partial pressure of chloroform in the chamber feed, CCl, was varied from 0% to 40%. Amorphous hydrogenated carbon films also containing silicon, oxygen, and small amounts of chlorine, a-C:H:Si:O:Cl, were produced at deposition rates of up to about 220 nm min−1 (for a CCl of 40%). Transmission infrared analyses revealed the presence of OH groups in chlorinated films, along with, among others, CH, C=C, Si-CH, Si-CH2, and Si-O-Si groups. As revealed by energy dispersive x-ray spectroscopy, the films could be doped with chlorine to a maximum of about 3 at. %. Surface morphology and roughness were examined using scanning electron microscopy and atomic force microscopy. Tauc band gaps, calculated from transmission ultraviolet-visible near infrared spectra, tend to decrease from ∼3.4 eV for unchlorinated films to around 2.5 eV for those doped with chlorine.